EFEKTIVITAS KEMITRAAN PT. PLN (Persero) RANTING RAPPANG DENGAN KUD DALAM PENAGIHAN REKENING LISTRIK - Rosnaini Daga (AkMen JURNAL ILMIAH, 2016)
: Is the problem in research partnerships PT. PLN (Persero) Branch Rappang with KUD in the collection of electricity bills has been effective The purpose of this study was to analyze the effectiveness of the partnership PT. PLN (Persero) Branch Rappang with KUD in the collection of electricity bills. Data collection methods used in this research is the method of documentation, by collecting documents or records billing realization of electricity bills in 2013 - 2014 in the payments received by KUD. The analytical method used in this research is qualitative descriptive analysis and effectiveness analysis. Descriptive qualitative analysis is an analysis that illustrates the effectiveness of the partnership PT. PLN (Persero) Branch Rappang in cooperation with KUD electricity billing. The results based on the analysis of the effectiveness of the partnership PT. PLN (Persero) Branch Rappang with KUD in the collection of electricity bills has been effective. Due to the realization in 2013 reached 95% and in 2014 amounted to 96.44%.